Feasibility Study of the Bicycle Sharing System as a Mode for Internal Movement of Employees: A Case Study - Kumar, Randhir; Brahampurya, Karunesh; Bhar, Chandan (Prabandhan: Indian Journal of Management, 2015)
Bicycle sharing systems allow people to hire a bicycle from a docking station for short-distance movement, typically one way, providing a substitute to the conventional means of movement, that is, private or public carriers (autos, taxies, etc.). In an integrated manufacturing industry, employees generally use private vehicles or company transport for internal movement within the organization, and the organization has to invest huge sums of money for purchasing or hiring of vehicles or has to pay T.A to the employees using their own means of transport. This paper attempted to show the effectiveness and feasibility of the bicycle sharing system in an integrated industry, which has a scattered layout. We also showed its effect on the cost of internal movement of employees in terms of fuel expenses.